High CO2-natural gas depressurization via CO2 flow loop facility: Design & engineering implementation - Shariff, A.M. (AIChE, 2019)
Sour natural gas resources contain high carbon dioxide content and require complex separation technologies to be developed. Cryogenic technologies such as cryogenic distillation and supersonic nozzle are among the identified technologies for natural gas conditioning, especially for offshore refinement. One of the challenges with offshore application of cryogenic technology is the absence of specific guideline in mitigating the blowdown philosophy which includes handling of CO2 solids. Depressurization using a CO2 closed flow loop facility was performed to further understand CO2 solid behavior under rapid depressurization. It is shown that CO2 solids formed in the pipelines and design of the flow loop is viable in order to handle the solids without any Health, Safety and Environmental (HSE) issues. Â© 2018. Any distribution of this work must maintain attribution to the author(s), title of the work, publisher.All right reserved.